A high performance modified polyurethane grouting material and preparation method thereof
By scientifically combining petroleum asphalt and other materials, high-performance modified polyurethane grouting materials were prepared, which solved the problems of insufficient adhesion and insufficient low-temperature toughness in crack repair of asphalt pavement in cold areas, and achieved good repair effect and durability.
Patent Information
- Application Number
- CN202411620566.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing polyurethane grouting materials have problems such as poor adhesion, insufficient low-temperature toughness and high cost in repairing cracks in cold areas, resulting in poor repair results and increasing maintenance costs and difficulty.
High-performance modified polyurethane grouting materials are used to prepare grouting materials with good low temperature resistance by scientifically combining petroleum asphalt, polyols, functional additives, polyisocyanates, catalysts, nanofillers and modifiers.
The material maintains good toughness and adhesion under low temperature conditions, effectively preventing cracks from further expanding, and improving the overall stability and durability of roads and bridges.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a high-performance modified polyurethane grouting material and a preparation method thereof. Background Art
[0002] In modern road construction, asphalt pavement is widely used in my country's highway and high-grade road systems due to its excellent performance. However, due to the long-term effects of heavy traffic, extreme temperature changes, ultraviolet radiation and natural weathering, asphalt pavement will inevitably suffer from various diseases, especially pavement cracks, which have become a key factor affecting road safety, comfort and service life.
[0003] The crack repair technologies currently available on the market have their own advantages, but all have limitations to varying degrees. For example, although micro-surfacing and thin-layer overlay technologies can cover cracks, they have limited repair effects on deep cracks; although the joint tape technology is easy to construct, it is easy to fall off or fail under extreme climatic conditions; and although the caulking repair technology is widely used, the existing caulking material products still have significant deficiencies in performance. Some caulking materials tend to become brittle in low temperature environments, causing the cracks after repair to crack again in the cold season, seriously affecting the repair effect; especially in extreme climatic conditions such as cold regions, it is more difficult to repair pavement cracks. The temperature difference in cold regions is large, and the temperature is negative for a long time in winter, which puts higher requirements on the low-temperature toughness, adhesion and anti-aging properties of the caulking materials. Traditional caulking materials often find it difficult to meet these requirements at the same time, causing the cracks after repair to crack again, increasing the maintenance cost and difficulty.
[0004] Polyurethane polymer materials have been widely used in many fields due to their excellent physical and mechanical properties, wear resistance, high and low temperature performance and good chemical stability. For example, the non-patent literature "Study on the Preparation and Performance Optimization of Polyurethane-Epoxy Resin Composite Modified Asphalt" and "Study on the Preparation Process of Polyurethane Modified Asphalt Based on Orthogonal Experiments" discloses the further study of the use of polyurethane modified asphalt from the composite effect of polyurethane and asphalt. However, in the field of asphalt pavement crack repair, the existing polyurethane grouting materials still have many shortcomings, such as weak adhesion to asphalt pavement, insufficient low-temperature toughness, and high cost. These problems limit the widespread application of polyurethane grouting materials in asphalt pavement crack repair in cold regions.
[0005] Based on the above background, the present invention aims to provide a high-performance modified polyurethane grouting material and a preparation method thereof. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, one of the objects of the present invention is to provide a high-performance modified polyurethane grouting material that can meet the maintenance needs of cold-region roads.
[0007] One of the purposes of the present invention is achieved by the following technical solution:
[0008] A high-performance modified polyurethane grouting material comprises the following components by weight: 120 parts of petroleum asphalt, 30-50 parts of polyol, 35-50 parts of functional additives, 60-90 parts of polyisocyanate, 0.1-2 parts of catalyst, 1-10 parts of nanofiller, and 5-15 parts of modifier; wherein the structural formula of the functional additive is:
[0009] .
[0010] Furthermore, the preparation of the functional additive comprises the following steps:
[0011]
[0012] (1) taking trans-4-hydroxycinnamic acid, 1,6-hexanediol and tetrabutyl titanate and reacting them in an inert atmosphere at 150-165°C for 12-16 hours, and treating them after the reaction to obtain an intermediate 1;
[0013] (2) taking intermediate 1, rosin acid and p-toluenesulfonic acid monohydrate and reacting them in an inert atmosphere at 140-150° C. for 12-16 seconds, and treating them after the reaction to obtain intermediate 2;
[0014] (3) taking intermediate 2, formic acid, hydrogen peroxide, and strong acid cation exchange resin and reacting them at 60-70°C for 6-8h, and treating them after the reaction to obtain intermediate 3;
[0015] (4) The intermediate 3, acetic anhydride and strong acid cation exchange resin are reacted at 110-120° C. for 6-8 hours. After the reaction is completed, the functional additive is obtained by treatment.
[0016] The preparation mechanism of the functional additive is as follows: the carboxyl group of trans-4-hydroxycinnamic acid and the alcoholic hydroxyl group of 1,6-hexanediol undergo esterification reaction to obtain intermediate 1; the phenolic hydroxyl group of intermediate 1 and the carboxyl group of rosin acid undergo esterification reaction to obtain intermediate 2; the double bond on intermediate 2 undergoes oxidation ring reaction through the combined action of hydrogen peroxide and formic acid to obtain intermediate 3; intermediate 3 undergoes ring-opening reaction with acetic anhydride to obtain the functional additive.
[0017] Furthermore, in step (1), the molar ratio of trans-4-hydroxycinnamic acid, 1,6-hexanediol and tetrabutyl titanate is 1: (0.48-0.50): (0.04-0.08).
[0018] Furthermore, in step (2), the molar ratio of the intermediate 1, rosin acid and p-toluenesulfonic acid monohydrate is 1:(2.2-2.5):(0.08-0.12).
[0019] Furthermore, in step (3), the molar ratio of the intermediate 2, formic acid and hydrogen peroxide is 1:(2.0-2.2):(2.5-2.8); and the mass ratio of the intermediate 2 to the strong acid cation exchange resin is 10-12:1.
[0020] Furthermore, in step (4), the molar ratio of the intermediate 3 to acetic anhydride is 1:(5-6); and the mass ratio of the intermediate 3 to the strong acid cation exchange resin is 10-12:1.
[0021] Furthermore, the polyisocyanate is hexadecane diisocyanate, and its preparation process includes the following steps: taking octadecane dioic acid, triethylamine, and diphenylphosphine azide into a solvent, reacting at 110-125° C. for 0.5-2 hours, and treating the reaction solution to obtain hexadecane diisocyanate.
[0022] Furthermore, the molar ratio of the octadecane dioic acid, triethylamine and diphenylphosphine azide is 1:(2.4-3.0):(2.2-2.5).
[0023] Furthermore, the polyol is one of polytetramethylene glycol and polyethylene glycol; the catalyst is an organic tin compound or an amine catalyst; the nanofiller is nanosilicon or nanotitanium; and the modifier is at least two of sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylamide, polyethyleneimine, and polyetheramine.
[0024] Furthermore, the organic tin compound is one of di-n-butyltin dilaurate and di-n-butyltin diacetate; the amine catalyst is one of N,N-dimethylaminoethoxyethoxyethanol and 5-(N,N-dimethyl)amino-3-methyl-1-pentanol.
[0025] The second object of the present invention is to provide a method for preparing a high-performance modified polyurethane grouting material.
[0026] The second object of the present invention is achieved by adopting the following technical solution:
[0027] The preparation method of the above-mentioned high-performance modified polyurethane grouting material comprises the following steps:
[0028] S1: Weigh each component according to the weight proportion, then add petroleum asphalt into a reaction kettle, heat until the petroleum asphalt is melted, then add the polyol, functional additives, and modifier, and stir at 60-80° C. for 1-2 hours to obtain a uniform mixture;
[0029] S2: adding the polyisocyanate, catalyst and nanofiller into the mixture, stirring at 50-80° C. for 2-4 hours and then curing for 2 hours to obtain the high-performance modified polyurethane grouting material.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention prepares an asphalt-based grouting material by scientifically combining carefully designed functional additives with polyisocyanates, petroleum asphalt, polyols, catalysts, nanofillers, and modifiers; the grouting material has good low-temperature resistance, can effectively prevent further expansion of cracks, and improve the overall stability and durability of roads and bridges.
[0032] The functional additive provided by the present invention contains a large number of ester groups and aromatic rings. The ester groups can interact with the polyurethane segments (such as van der Waals forces and hydrogen bonds). This interaction not only improves the compatibility between the additive, the polyurethane matrix and the asphalt matrix, but also promotes the close bonding between molecules, which helps the grouting material to maintain uniformity and stability during mixing and use, thereby affecting the overall performance of the grouting material. The flexible alkyl chain and aromatic ring of the functional additive can increase the free movement space of the molecular chain, weaken the interaction force between the molecular chains, and make the material more easily deformed and not easy to break when subjected to force, thereby reducing the heat resistance (softening point) of the grouting material, improving the flow performance (flow value), reducing the viscosity and elastic recovery rate of the grouting material, improving its fluidity, and increasing the cone penetration value of the material.
[0033] In addition, the hexadecane diisocyanate selected in the present invention has a long-chain structure. Under low temperature conditions, this long-chain structure can effectively maintain the toughness and elasticity of the grouting material and prevent performance degradation caused by temperature drop; the modifier selected in the present invention contains more active functional groups, such as hydroxyl and amino groups, thereby increasing the compatibility with polyurethane, and then synergizing with polyurethane to effectively maintain the toughness of the grouting material. DETAILED DESCRIPTION
[0034] Below, in conjunction with specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.
[0035] Example 1
[0036] A high-performance modified polyurethane grouting material comprises the following components by weight: 120 parts of petroleum asphalt, 40 parts of polytetramethylene ether glycol, 42 parts of functional additives, 72 parts of polyisocyanate, 1.2 parts of di-n-butyltin dilaurate, 5 parts of nano silicon, 4 parts of sodium carboxymethyl cellulose and 4 parts of polyvinyl alcohol.
[0037] The preparation process of the functional additives is as follows:
[0038]
[0039] (1) Place trans-4-hydroxycinnamic acid (100 mmol), 1,6-hexanediol (48 mmol) and tetrabutyl titanate (4 mmol) in a reaction flask, stir evenly at room temperature in a nitrogen atmosphere, and then heat to 158°C for 13 h. Cool the reaction solution to room temperature, quench the reaction with saturated sodium bicarbonate, add ethyl acetate to the reaction solution, separate the organic phase, wash the organic phase with deionized water, dry and concentrate the organic phase, and purify it with a column (eluent, petroleum ether: ethyl acetate = 1:1) to obtain intermediate 1.
[0040] (2) Intermediate 1 (100 mmol), rosin acid (250 mmol) and p-toluenesulfonic acid monohydrate (10 mmol) were placed in a reaction flask. Under a nitrogen atmosphere, the mixture was stirred evenly at room temperature and then heated to 140°C for reaction for 10 h. The reaction was quenched with deionized water and ethyl acetate was added to the reaction solution. After separation, the ethyl acetate phase was distilled to obtain Intermediate 2.
[0041] (3) Take intermediate 2 (50 mmol) and strong acid cation exchange resin (5 g) in a reaction flask, heat the reaction flask to 65°C, then mix formic acid (100 mmol) and 30% hydrogen peroxide (250 mmol) and add them dropwise to the reaction flask. After the addition is complete, react at 65°C for 6 h, quench the reaction with deionized water, and then add ethyl acetate to the reaction solution. After separation, distill the ethyl acetate phase to obtain intermediate 3.
[0042] (4) Take intermediate 3 (50 mmol), acetic anhydride (300 mmol), and strong acid cation exchange resin (5 g), stir them evenly at room temperature, and then heat them to 115°C to react for 6 hours. After quenching the reaction with deionized water, add ethyl acetate to the reaction solution, separate the liquids, and distill the ethyl acetate phase to obtain a functional additive.
[0043] The above functional additives 1 H NMR (C 72 H 94 O 16 , 400MHz, DMSO- d6 ): δ 7.28-7.17 (m, 10H), 6.47 (d, 2H), 5.75 (d, 2H), 5.50 (td, 2H), 4.06 (t, 4H), 2.42-2.12 (m, 62H), 0.86 (d, 12H); [M+H] + m / z: 1214.65, ESI-MS (m / z): 1214.66.
[0044] Among them, the polyisocyanate is hexadecane diisocyanate, and its preparation process is as follows:
[0045] Octadecanedioic acid (50 mmol) and triethylamine (120 mmol) were added to toluene (100 mL). After stirring, diphenylphosphine azide (110 mmol) was added to the mixed system in batches. After the addition was completed, the reaction solution was stirred evenly and then heated to 120°C for 1 h. Water was added to quench the reaction. The aqueous phase was extracted with ethyl acetate, and then 20 mL of 3% sodium hypochlorite solution was used to stir the organic phase for 5 min and then separated. The organic phase was dried and concentrated to obtain hexadecane diisocyanate (CAS: 102176-54-5).
[0046] The above hexadecane diisocyanate 1 H NMR (C 18 H 32 N2O2, 400MHz, DMSO- d6 ): δ 3.41 (t, 4H), 1.59-1.55 (m, 4H), 1.31-1.21 (m, 24H); [M+H] + m / z: 309.25, ESI-MS (m / z): 309.25.
[0047] This embodiment also provides the following preparation process of the above-mentioned high-performance modified polyurethane grouting material:
[0048] S1: Weigh the components according to the above ratio, then add petroleum asphalt into a reaction kettle, heat it to melt it, then add polytetramethylene glycol, functional additives, sodium carboxymethyl cellulose, and polyvinyl alcohol thereto, stir at 70°C for 1.5h to obtain a uniform mixture;
[0049] S2: Add polyisocyanate, di-n-butyltin dilaurate and nano-silicon to the above mixture, stir at 65°C for 3h and then cure for 2h to obtain a high-performance modified polyurethane grouting material.
[0050] Example 2
[0051] A high-performance modified polyurethane grouting material includes the following components by weight: 120 parts of petroleum asphalt, 30 parts of polyethylene glycol, 35 parts of functional additives, 60 parts of polyisocyanate, 0.1 parts of N,N-dimethylaminoethoxyethoxyethanol, 1 part of nano titanium, 2.5 parts of polyacrylamide, and 2.5 parts of polyethyleneimine. The preparation process is as follows:
[0052] (1) Place trans-4-hydroxycinnamic acid (100 mmol), 1,6-hexanediol (50 mmol), and tetrabutyl titanate (8 mmol) in a reaction flask, stir evenly at room temperature in a nitrogen atmosphere, and then heat to 150°C for 16 h. Cool the reaction solution to room temperature, quench the reaction with saturated sodium bicarbonate, and then add ethyl acetate to the reaction solution. Separate the organic phase, wash the organic phase with deionized water, dry and concentrate the organic phase, and purify it with a column (eluent, petroleum ether: ethyl acetate = 1:1) to obtain intermediate 1.
[0053] (2) Intermediate 1 (100 mmol), rosin acid (220 mmol), and p-toluenesulfonic acid monohydrate (12 mmol) were placed in a reaction flask. Under a nitrogen atmosphere, the mixture was stirred evenly at room temperature and then heated to 145°C for 16 h. The reaction was quenched with deionized water and ethyl acetate was added to the reaction solution. After separation, the ethyl acetate phase was distilled to obtain Intermediate 2.
[0054] (3) Take intermediate 2 (50 mmol) and strong acid cation exchange resin (5 g) in a reaction flask, heat the reaction flask to 65°C, then mix formic acid (110 mmol) and 30% hydrogen peroxide (280 mmol) and add them dropwise to the reaction flask. After the addition is complete, react at 60°C for 8 h, quench the reaction with deionized water, and then add ethyl acetate to the reaction solution. After separation, distill the ethyl acetate phase to obtain intermediate 3.
[0055] (4) Take intermediate 3 (50 mmol), acetic anhydride (250 mmol), and strong acid cation exchange resin (5 g), stir them evenly at room temperature, and then heat them to 110°C to react for 8 hours. After quenching the reaction with deionized water, add ethyl acetate to the reaction solution, separate the liquids, and distill the ethyl acetate phase to obtain a functional additive. 1 H NMR and MS showed that the structure was consistent with that of Example 1.
[0056] Among them, the polyisocyanate is hexadecane diisocyanate, and its preparation process is as follows:
[0057] Take octadecane dioic acid (50 mmol) and triethylamine (150 mmol) and add them to toluene (100 mL). After stirring evenly, diphenylphosphine azide (125 mmol) is added to the mixed system in batches. After the addition is completed, the reaction solution is stirred evenly and then heated to 110°C and reacted for 2 hours. Water is added to quench the reaction, the aqueous phase is extracted with ethyl acetate, and then 25 mL of 3% sodium hypochlorite solution is used to stir the organic phase for 5 minutes and then separate the liquids. The organic phase is dried and concentrated to obtain hexadecane diisocyanate. 1 H NMR and MS showed that the structure was consistent with that of Example 1.
[0058] This embodiment also provides the following preparation process of the above-mentioned high-performance modified polyurethane grouting material:
[0059] S1: Weigh the components according to the above ratio, then add petroleum asphalt into a reaction kettle, heat it to melt it, then add the polyethylene glycol, functional additives, polyacrylamide, and polyethyleneimine thereto, and stir at 70° C. for 1.5 h to obtain a uniform mixture;
[0060] S2: adding the polyisocyanate, N,N-dimethylaminoethoxyethoxyethanol and nano-titanium to the above mixture, stirring at 65° C. for 3 hours and then curing for 2 hours to obtain a high-performance modified polyurethane grouting material.
[0061] Example 3
[0062] A high-performance modified polyurethane grouting material includes the following components by weight: 120 parts of petroleum asphalt, 50 parts of polytetramethylene glycol, 50 parts of functional additives, 90 parts of polyisocyanate, 2 parts of di-n-butyltin diacetate, 10 parts of nano-silicon, 7.5 parts of sodium carboxymethyl cellulose, and 7.5 parts of polyetheramine. The preparation process is as follows:
[0063] (1) Place trans-4-hydroxycinnamic acid (100 mmol), 1,6-hexanediol (49 mmol), and tetrabutyl titanate (6 mmol) in a reaction flask, stir evenly at room temperature in a nitrogen atmosphere, and then heat to 165°C for 12 h. Cool the reaction solution to room temperature, quench the reaction with saturated sodium bicarbonate, and then add ethyl acetate to the reaction solution. Separate the organic phase, wash the organic phase with deionized water, dry and concentrate the organic phase, and purify it with a column (eluent, petroleum ether: ethyl acetate = 1:1) to obtain intermediate 1.
[0064] (2) Intermediate 1 (100 mmol), rosin acid (230 mmol), and p-toluenesulfonic acid monohydrate (8 mmol) were placed in a reaction flask. Under a nitrogen atmosphere, the mixture was stirred evenly at room temperature and then heated to 150°C for 12 h. The reaction was quenched with deionized water and ethyl acetate was added to the reaction solution. After separation, the ethyl acetate phase was distilled to obtain Intermediate 2.
[0065] (3) Take intermediate 2 (50 mmol) and strong acid cation exchange resin (5 g) in a reaction flask, heat the reaction flask to 65°C, then mix formic acid (105 mmol) and 30% hydrogen peroxide (265 mmol) and add them dropwise to the reaction flask. After the addition is complete, react at 70°C for 6 h, quench the reaction with deionized water, and then add ethyl acetate to the reaction solution. After separation, distill the ethyl acetate phase to obtain intermediate 3.
[0066] (4) Take intermediate 3 (50 mmol), acetic anhydride (280 mmol), and strong acid cation exchange resin (5 g), stir them evenly at room temperature, heat them to 120°C, react for 6 h, quench the reaction with deionized water, and then add ethyl acetate to the reaction solution. After separation, distill the ethyl acetate phase to obtain a functional additive. 1 H NMR and MS showed that the structure was consistent with that of Example 1.
[0067] Among them, the polyisocyanate is hexadecane diisocyanate, and its preparation process is as follows:
[0068] Take octadecane dioic acid (50 mmol) and triethylamine (135 mmol) and add them to toluene (100 mL). After stirring evenly, diphenylphosphine azide (135 mmol) is added to the mixed system in batches. After the addition is completed, the reaction solution is stirred evenly and then heated to 125°C and reacted for 0.5 h. Water is added to quench the reaction. After the aqueous phase is extracted with ethyl acetate, 20 mL of 3% sodium hypochlorite solution and the organic phase are stirred for 5 min and then separated. The organic phase is dried and concentrated to obtain hexadecane diisocyanate. 1 H NMR and MS showed that the structure was consistent with that of Example 1.
[0069] This embodiment also provides the following preparation process of the above-mentioned high-performance modified polyurethane grouting material:
[0070] S1: weighing each component according to the above ratio, then adding petroleum asphalt into a reaction kettle, heating it to melt it, and then adding the polytetramethylene ether glycol, functional additives, sodium carboxymethyl cellulose, and polyetheramine thereto and stirring at 70° C. for 1.5 hours to obtain a uniform mixture;
[0071] S2: adding the polyisocyanate, di-n-butyltin diacetate and nano-silicon to the above mixture, stirring at 65° C. for 3 hours and then curing for 2 hours to obtain a high-performance modified polyurethane grouting material.
[0072] Comparative Example 1
[0073] A polyurethane grouting material, which is different from Example 1 in that the functional additive is omitted.
[0074] Comparative Example 2
[0075] A polyurethane grouting material, which differs from Example 1 in that polyisocyanate is replaced by an equal amount of hexamethylene diisocyanate.
[0076] Comparative Example 3
[0077] A polyurethane grouting material, which differs from Example 1 in that a modifier is omitted.
[0078] Performance Testing
[0079] The polyurethane grouting materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were sampled, and the following performance tests were performed on the samples according to JT / T 740-2015 "Pavement Heating Sealant": cone penetration - the depth of a standard cone vertically penetrating into the sample under specified experimental conditions, measured in 0.1 mm; softening point - the temperature at which an amorphous polymer begins to soften, measured in degrees Celsius (°C); flow value - the length of the sample flowing under specified experimental conditions, measured in mm; elastic recovery rate - the percentage of deformation that can be recovered by the sample under specified experimental conditions, measured in percentage (%); low-temperature tensile test - the sample was placed in a low-temperature device and subjected to a tensile test at a constant temperature (-30°C); 135°C viscosity; and tackiness.
[0080] Test Example 1
[0081] Heat resistance test
[0082] (1) The softening point of the sample was tested according to the T0606 asphalt softening point test in JTG E20-2011, and the results are shown in Table 1. The softening point is used to characterize the heat resistance of the sample. The softening point of the severe cold potting glue is usually higher to ensure that it will not become brittle or lose elasticity due to temperature drop under extremely cold conditions; a higher softening point helps to improve the high temperature resistance of the potting glue, and also helps to maintain its stability at low temperatures.
[0083] (2) The flow value of the sample was tested according to the flow test in JT / T 740-2015, and the results are shown in Table 1. At low temperatures, the flow value of the severe cold potting glue needs to be controlled within a certain range (≤5mm) to prevent the material from flowing or spreading to unnecessary areas before low-temperature curing; at the same time, the flow value also affects the bonding effect between the potting glue and the crack wall.
[0084] Table 1 Softening point and flow value of samples
[0085]
[0086] It can be seen from Table 1 that the cone penetration and flow value of Examples 1 to 3 both meet the technical indicators required by JT / T 740-2015 "Pavement Heating Sealant". Comparative Example 1 does not add functional additives, and its softening point is higher than that of Examples 1 to 3, and its flow value is lower than that of Examples 1 to 3; this is because the flexible alkyl chain and aromatic ring of the functional additive can increase the free movement space of the molecular chain, weaken the interaction force between the molecular chains, make the material more easily deformed and not easy to break when subjected to force, reduce the heat resistance (softening point) of the grouting material, and improve the flow performance (flow value). The softening point and flow value of Comparative Examples 2 and 3 are almost the same as those of Examples 1 to 3.
[0087] Test Example 2
[0088] Flexibility and viscosity testing
[0089] (1) The cone penetration of the sample was tested using a cone penetration tester according to the cone penetration test in JT / T 740-2015. The results are shown in Table 2. The cone penetration of severe cold potting glue is usually adjusted within a specific range (90~150, unit: 0.1mm) to ensure that the appropriate viscosity is maintained at low temperatures to facilitate construction and fill cracks; a higher cone penetration may mean that it can still maintain good fluidity under extremely cold conditions, while a lower cone penetration helps prevent the material from excessively flowing at high temperatures.
[0090] (2) According to the elastic recovery test in JT / T 740-2015, the elastic recovery of the sample was tested using an elasticity tester. The results are shown in Table 2. The severe cold potting compound needs to have a higher elastic recovery rate to cope with the pavement shrinkage and deformation caused by low temperatures. Under extremely cold conditions, the pavement material may deform significantly due to temperature changes, so the potting compound needs to have good elastic recovery ability to maintain the sealing effect of the cracks.
[0091] (3) According to the low-temperature tensile test in JT / T 740-2015, the low-temperature tensile properties of the samples were tested using a tensile testing machine. The results are shown in Table 2. The severe cold potting glue needs to maintain a certain tensile property at extremely low temperatures (-30°C) (JT / T740-2015 "Road Heating Sealant" has low-temperature tensile requirements for severe cold potting glue: -30°C, 150%, 3 cycles, qualified; 150% stretching is 22.5mm) to ensure that the cracks will not reopen or expand at low temperatures while meeting the requirements of multiple cyclic loading.
[0092] (4) The viscosity of the high performance modified polyurethane grouting material of the present invention at 135°C was measured by the rotation method. The results are shown in Table 2.
[0093] Table 2 Cone penetration, elastic recovery, low temperature tensile strength, and 135℃ viscosity of the samples
[0094]
[0095] As shown in Table 2, Examples 1 to 3 meet the technical indicators required by JT / T 740-2015 "Road Heating Sealant" in terms of cone penetration, elastic recovery rate and low-temperature tensile strength. The viscosity at 135°C in Examples 1 to 3 is relatively low, which is convenient for construction. Comparative Example 1 does not add functional additives, and its cone penetration is lower than that of Examples 1 to 3, its elastic recovery rate is higher than that of Examples 1 to 3, and its low-temperature tensile performance is slightly inferior to that of Examples 1 to 3 (it cannot meet the technical indicators of severe cold-type sealants in JT / T 740-2015 "Road Heating Sealant"), and its viscosity at 135°C is significantly greater than that of Examples 1 to 3. This is because the flexible alkyl chain and aromatic ring of the functional additive can increase the free movement space of the molecular chain, weaken the interaction force between the molecular chains, and make the material easier to slide and flow when subjected to force, thereby reducing the viscosity and elastic recovery rate of the grouting material, and improving its fluidity, thereby increasing the cone penetration value of the material, and the material is also easier to deform and not easy to break when subjected to force, thereby improving the tensile performance of the grouting material.
[0096] In Comparative Example 2, the hexadecane diisocyanate in step S2 of Example 1 is replaced with an equal amount of hexamethylene diisocyanate, and its low-temperature tensile properties are significantly weaker than those of Examples 1 to 3, and other properties are almost the same as those of Examples 1 to 3. This is because hexadecane diisocyanate has a long-chain structure, which can effectively maintain the toughness and elasticity of the grouting material under low temperature conditions and prevent performance degradation caused by temperature drop.
[0097] Comparative Example 3 omits the modifier in step S1 of Example 1, and its low-temperature tensile properties are significantly weaker than those of Examples 1 to 3, and other properties are almost the same as those of Examples 1 to 3. This is because the modifier contains more active functional groups, such as hydroxyl and amino groups, which increase the compatibility with polyurethane, and then synergize with polyurethane to effectively maintain the toughness of the grouting material.
[0098] Test Example 3
[0099] Adhesion and toughness test
[0100] It is carried out in accordance with JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" T0624.
[0101] Table 3 Adhesion and toughness
[0102]
[0103] It can be seen from Table 3 that: Comparative Example 1 does not add functional additives, Comparative Example 2 replaces the hexadecane diisocyanate in step S2 of Example 1 with an equal amount of hexamethylene diisocyanate, and Comparative Example 3 omits the modifier in step S1 of Example 1. The viscosity and toughness of the three groups are lower than those of Examples 1 to 3. The above results show that the interaction between the functional additives and the polyurethane jointly affects the viscosity and toughness of the grouting material of the present invention.
[0104] From the results of test examples 1 to 3, it can be seen that the cooperation of functional additives, hexadecane diisocyanate, modifiers and other components of common potting glue, such as petroleum asphalt, polyols, catalysts and nanofillers, can improve the cone penetration and flow value, reduce the softening point and elastic recovery rate of the grouting material, improve the low-temperature tensile properties, and improve the viscosity and toughness, thereby preparing a grouting material that can meet the maintenance needs of cold-region roads.
[0105] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A high-performance modified polyurethane grouting material, characterized in that: The invention comprises the following components by weight: 120 parts of petroleum asphalt, 30-50 parts of polyol, 35-50 parts of functional additives, 60-90 parts of polyisocyanate, 0.1-2 parts of catalyst, 1-10 parts of nanofiller, and 5-15 parts of modifier; the polyisocyanate is hexadecane diisocyanate, the modifier is at least two of sodium carboxymethyl cellulose, polyvinyl alcohol, polyacrylamide, polyethyleneimine, and polyetheramine, and the structural formula of the functional additive is: 。 2. The high performance modified polyurethane grouting material according to claim 1, characterized in that: The preparation of the functional additive comprises the following steps: (1) taking trans-4-hydroxycinnamic acid, 1,6-hexanediol and tetrabutyl titanate and reacting them in an inert atmosphere at 150-165°C for 12-16 hours, and treating them after the reaction to obtain an intermediate 1; (2) intermediate 1, rosin acid and p-toluenesulfonic acid monohydrate are reacted in an inert atmosphere at 140-150°C for 12-16 hours, and after the reaction is completed, intermediate 2 is obtained by treatment; (3) taking intermediate 2, formic acid, hydrogen peroxide, and strong acid cation exchange resin and reacting them at 60-70°C for 6-8h, and treating them after the reaction to obtain intermediate 3; (4) The intermediate 3, acetic anhydride and strong acid cation exchange resin are reacted at 110-120° C. for 6-8 hours. After the reaction is completed, the functional additive is obtained by treatment.
3. The high performance modified polyurethane grouting material according to claim 2, characterized in that: The molar ratio of trans-4-hydroxycinnamic acid, 1,6-hexanediol and tetrabutyl titanate in step (1) is 1: (0.48-0.50): (0.04-0.08).
4. The high performance modified polyurethane grouting material according to claim 2, characterized in that: In step (2), the molar ratio of the intermediate 1, rosin acid and p-toluenesulfonic acid monohydrate is 1:(2.2-2.5):(0.08-0.12).
5. The high performance modified polyurethane grouting material according to claim 2, characterized in that: In step (3), the molar ratio of the intermediate 2, formic acid and hydrogen peroxide is 1:(2.0-2.2):(2.5-2.8); the mass ratio of the intermediate 2 to the strong acid cation exchange resin is 10-12:
1.
6. The high performance modified polyurethane grouting material according to claim 2, characterized in that: In step (4), the molar ratio of the intermediate 3 to acetic anhydride is 1:(5-6); the mass ratio of the intermediate 3 to the strong acid cation exchange resin is 10-12:
1.
7. The high performance modified polyurethane grouting material according to claim 1, characterized in that: The preparation process of hexadecane diisocyanate comprises the following steps: taking octadecane dioic acid, triethylamine and diphenylphosphine azide into a solvent, reacting at 110-125° C. for 0.5-2 hours, and treating the reaction solution to obtain hexadecane diisocyanate.
8. The high performance modified polyurethane grouting material according to claim 7, characterized in that: The molar ratio of the octadecane dioic acid, triethylamine and diphenylphosphine azide is 1:(2.4-3.0):(2.2-2.5).
9. The high performance modified polyurethane grouting material according to claim 1, characterized in that: The polyol is one of polytetramethylene glycol and polyethylene glycol; the catalyst is an organic tin compound or an amine catalyst; and the nano filler is nano silicon or nano titanium.
10. The method for preparing the high performance modified polyurethane grouting material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Weighing each component according to the weight proportion, then adding petroleum asphalt into a reaction kettle, heating until the petroleum asphalt is melted, then adding the polyol, functional additives, and modifier, stirring at 60-80° C. for 1-2 hours to obtain a mixture; S2: adding the polyisocyanate, catalyst and nanofiller to the mixture, stirring at 50-80° C. for 2-4 hours, and curing for 2 hours to obtain the high-performance modified polyurethane grouting material.
Citation Information
Patent Citations
High-viscosity modified asphalt and preparation method thereof
CN116790129A
Polyurethane adhesive and preparation method thereof
CN118879263A